E-Government and Malaysia: A Theoretical Consideration - Morshidi, Azizan H; Hamid, Fazli Abd (SOSIOHUMANIKA, 2010)
ABSTRACT: This paper does not try to paint a bleak picture of e-Government initiative in developing countries or Malaysia in particular. Nonetheless, such limitations, if any, must not be left unnoticed. Indisputably, notions of âsuccessâ and âfailureâ are indeed highly subjective issues. The outcome of something as difficult and complex to achieve as government reform, or higher levels of civic engagement by means of electronic medium, may not be sensed immediately. These agencies must also be ready to transform mindsets, systems, and processes even if this may decrease their autonomy. Boundaries, silos, and counters will have to be torn down and done away as clients move online. Communications with the government via e-mails and other electronic channels will be made a mere routine norm, delivered to the public clients any time of the day across any time zone and in any continent. The implementation of a fully connected Malaysian government also requires empowering the government workforce. Bureaucratic agencies must focus their interest to empowering employees by providing them the tools to perform and deliver their duties better and from any workspace. Therefore, there is an urgent need to make human capital planning a strategic element in the agenciesâ initiatives. An effective and fully connected Malaysian e-Government initiative poses challenges on how they might devise policies to spur and inspire local innovation and on how they might integrate which technology to achieve their objectives to a greater degree.Key words: e-Government, Malaysian nation-state, Information and Communication Technology, bureaucratic reform, and effective management.Â Â About the Authors: Azizan H. Morshidi is a Lecturer at the Industrial Relations Program, School of Social Sciences UMS (Malaysia University of Sabah). Fazli Abd Hamid is a Senior Lecturer at the Industrial Relations Program, School of Social Sciences UMS (Malaysia University of Sabah). For academic purposes, they can be duly contacted at: azizanm@gmail.com and ag4477@msn.comHow to cite this article? Morshidi, Azizan H. & Fazli Abd Hamid. (2010). âE-Government and Malaysia: A Theoretical Considerationâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.3, No.2 [November], pp.305-324. Bandung, Indonesia: Minda Masagi Press, UNIPA Surabaya, and UMS Kota Kinabalu, Malaysia, ISSN 1979-0112. Chronicle of article: Accepted (September 10, 2010); Revised (October 15, 2010); and Published (November 20, 2010). Â  Â